Identification of the Highly Polymorphic Prion Protein Gene (PRNP) in Frogs (Rana dybowskii) - Chang-Su Han; Sae-Young Won; Sang-Hun Park; Yong-Chan Kim (Animals)
Prion diseases are fatal neurodegenerative diseases that can be transmitted by infectious protein particles, PrPScs, encoded by the endogenous prion protein gene (PRNP). The origin of prion seeds is unclear, especially in non-human hosts, and this identification is pivotal to preventing the spread of prion diseases from host animals. Recently, an abnormally high amyloid propensity in prion proteins (PrPs) was found in a frog, of which the genetic variations in the PRNP gene have not been investigated. In this study, genetic polymorphisms in the PRNP gene were investigated in 194 Dybowski’s frogs using polymerase chain reaction (PCR) and amplicon sequencing. We carried out in silico analyses to predict functional alterations according to non-synonymous single nucleotide polymorphisms (SNPs) using PolyPhen-2, PANTHER, SIFT, and MutPred2. We used ClustalW2 and MEGA X to compare frog PRNP and PrP sequences with those of prion-related animals. To evaluate the impact of the SNPs on protein aggregation propensity and 3D structure, we utilized AMYCO and ColabFold. We identified 34 novel genetic polymorphisms including 6 non-synonymous SNPs in the frog PRNP gene. The hydrogen bond length varied at codons 143 and 207 according to non-synonymous SNPs, even if the electrostatic potential was not changed. In silico analysis predicted S143N to increase the aggregation propensity, and W6L, C8Y, R211W, and L241F had damaging effects on frog PrPs. The PRNP and PrP sequences of frogs showed low homology with those of prion-related mammals. To the best of our knowledge, this study was the first to discover genetic polymorphisms in the PRNP gene in amphibians.